1972
DOI: 10.1111/j.1469-7998.1972.tb01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological studies on crater lakes in West Cameroon Fishes of Barombi Mbo

Abstract: In the West Cameroonian crater lake, Barombi Mbo, and its inflowing stream there are 17 species of fishes, of which 12, including the 11 cichlids, appear to be endemic. We give a systematic account of the endemics, including four new species and two new genera, Konia and Myaka. The ecology of the lake is described in relation to the feeding biology of the fishes, studied by underwater observation in the lake and the examination of stomach contents. The cichlids in Barombi Mbo probably evolved there from two or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 17 publications
3
97
0
1
Order By: Relevance
“…This gene is otherwise known to be used exclusively during the larval period in Nile tilapia (Spady et al, ). Similarly, we detected expression of the UV‐sensitive SWS1 opsin (expressed in larvae of Nile tilapia; Spady et al, ) in one species, S. steinbachi , an algae/debris feeder and the most herbivorous species from the lake (Baldo et al, ; Trewavas et al, ; and personal observation of higher plant feeding). The link between herbivory and SWS1 expression is in agreement with the observations of O'Quin et al () in Malawi cichlids, where algae scrapers (together with zooplanktivores) have increased expression levels of SWS1.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This gene is otherwise known to be used exclusively during the larval period in Nile tilapia (Spady et al, ). Similarly, we detected expression of the UV‐sensitive SWS1 opsin (expressed in larvae of Nile tilapia; Spady et al, ) in one species, S. steinbachi , an algae/debris feeder and the most herbivorous species from the lake (Baldo et al, ; Trewavas et al, ; and personal observation of higher plant feeding). The link between herbivory and SWS1 expression is in agreement with the observations of O'Quin et al () in Malawi cichlids, where algae scrapers (together with zooplanktivores) have increased expression levels of SWS1.…”
Section: Discussionmentioning
confidence: 56%
“…Tissue samples were collected in crater lake Barombi Mbo (coordinate: 9°22′E, 4°38′N; Trewavas et al, ), South‐West Cameroon, between 2013 and 2018 (research permit numbers: 0000047,49/MINRESI/B00/C00/C10/nye, 0000116,117/MINRESI/B00/C00/C10/C14, 000002‐3/MINRESI/B00/C00/C10/C11, 0000032,48‐50/MINRESI/B00/C00/C10/C12). Between 8 and 16 individuals per each of all 11 cichlid species were collected using gill nets and selective capturing by snorkelling in the shallow‐water zone, and with gill nets and minnow traps for the deeper zone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These co-authors therefore suggested that such data be expressed in percentage live weights. The high representation of the tilapias could be attributed to their high reproductive potential (Trewavas et al, 1972;Hepher and Pruginin, 1981) coupled with practice of parental care in that family (Beveridges and McAndrew, 2000).…”
Section: Discussionmentioning
confidence: 99%